The agro-physiological characteristics of three rice varieties affected by water depth in the coastal agricultural land of Yogyakarta, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Nasrudin, Kurniasih B. 2021. The agro-physiological characteristics of three rice varieties affected by water depth in the coastal agricultural land of Yogyakarta, Indonesia. Biodiversitas 22: 3656-3662. Coastal agricultural land has many obstacles of abiotic stress for plant cultivation, including waterlogging, strong wind, and high salt concentration. Therefore, the use of adaptive rice varieties, as well as good land management, are expected to be a solution for rice cultivation in the coastal agricultural land. The objective of this study was to examine the agro-physiological characteristics of three rice varieties planted in coastal agricultural land which were affected by water salinity up to more than 10 dS m-1. This study was conducted from February to July 2017 at Tirtohargo, Bantul District, Special Region of Yogyakarta. The experiment was arranged in a split-plot design, with the depths of sunken-bed as a main plot consisted of 25 cm and 50 cm, and variety as a subplot consisted of IR 64, Inpara 4, and Dendang. The experiment results showed that Dendang had the highest growth and yield in coastal agricultural land compared to Inpara 4 and IR64. The highest value is indicated in plant height, leaf area, proline content, and productivity. The depths 50 cm of sunken-bed increased leaf area and proline content, whereas the depths of 25 cm sunken-bed increased productivity. Dendang showed better agro-physiological activity and had the highest productivity. The depths of 50 cm increased several parameters in agro-physiological characteristics, however, the depths of 25 cm increased grain yield. Among the varieties tested, in salinity, the highest growth and yield variables were shown by Dendang, followed by IR 64 and Inpara 4.
Keywords: abiotic stress; marginal land; paddy; salinity